(3cJGH fbO GdfKQs - (3CHh ehSi SdjeGf Hf eMeO GdNGdYj GdfMhjs
(3ChdgG (B:s
(3Ef Chd eG CaJJM dg GddHjH cJGHg eG EaJJM Gddg Hg GdbQBf aGdMeO ddg TcQkG dfYeJg CeG HYO aEfc PcQJ di hbhac YdicJGH YeQh Hf GdLGMX GdPi SeGg cJGH GdHjGf hGdJHjjf s
(3BNQgG (B:s
(3adjS fSHI gPG GdTGYQ aCJi HPdc ddSLY dG dEaGOI eYfi HeG CJi Hg efgG BNQ cJGH fbO GdfKQ s
(3hgj ef cJH CejQ GdeDefjf RjOGf GdMSjfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1403s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs